Temporal monitoring of fumarole composition at Santorini volcano (Greece) highlights a quiescent state after the 2011–2012 unrest - Bernard, Alexis; Battani, Anne; Rizzo, Andrea Luca; Balci, Uğur; Györe, Domokos; D’Alessandro, Walter; Callot, Jean-Paul; Kyriakopoulos, Konstantinos; Pujol, Magali (Frontiers in Earth Science, 2024)
Santorini Island (Greece) is an active volcano which has alternated between dormant and active periods over the last 650,000 years with the latest volcanic disturbances occurring in 2011-2012. Here we report a geochemical survey of fumarolic gases collected at Nea Kameni islet located in the center of the caldera over the period 2015-2022 in order to study the activity of the volcano and changes in hydrothermal conditions. This period is marked by the absence of significant geochemical anomalies compared to the volcanic unrest of 2011-2012, implying that no new magma upwelling has occurred. This is evident from the low CO2/CH4 ratio and H2 concentration of fumaroles. An increase of the atmospheric contribution in gases after the 2011-2012 unrest suggests a decrease of the deep gas flow and the chemical and C-He-isotope compositions are compatible with a model of Rayleigh fractionation in which CO2 2 dissolves in water at decreasing temperatures over time. These results are consistent with temperature estimates obtained using the H2/N2 geothermometer, seismic and geodetic evidences. This implies a slowing of the degassing of the hydrothermal/volcanic system and a cooling of the magma injected at shallow depth in 2011-2012.